2023
DOI: 10.1021/acsami.3c09321
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobicity Tuned Polymeric Redox Materials with Solution-Specific Electroactive Properties for Selective Electrochemical Metal Ion Recovery in Aqueous Environments

Kai-Jher Tan,
Satoshi Morikawa,
Ali Hemmatifar
et al.

Abstract: Adaptable redox-active materials hold great potential for electrochemically mediated separation processes via targeted molecular recognition and reduced energy requirements. This work presents molecularly tunable vinylferrocene metallopolymers (P-(VFc-co-X)) with modifiable operating potentials, charge storage capacities, capacity retentions, and analyte affinities in various electrolyte environments based on the hydrophobicity of X. The styrene (St) co-monomer impedes hydrophobic anions from ferrocene access,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…The effects of different comonomers and their quantities on the pseudocapacitances of the ferrocene copolymers suggest that the hydrophobicity of the comonomer impacts the accessibility of the VFc units to aqueous media and their subsequent oxidation. Correspondingly, it has previously been reported that the presence of a hydrophobic comonomer in vinylferrocene copolymers reduces their overall pseudocapacitance . This hypothesis was also supported by the roughly equivalent size properties of the three comonomers (Table ), as well as the comparable homogeneous cyclic voltammogram responses (Figure a) and calculated diffusion coefficients (Figure b and Table S1) of the resulting copolymers in organic media, all of which imply that the aforementioned dissimilarities in heterogeneous electrochemical behavior between the polymers are not a result of molecular size or electronic properties.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…The effects of different comonomers and their quantities on the pseudocapacitances of the ferrocene copolymers suggest that the hydrophobicity of the comonomer impacts the accessibility of the VFc units to aqueous media and their subsequent oxidation. Correspondingly, it has previously been reported that the presence of a hydrophobic comonomer in vinylferrocene copolymers reduces their overall pseudocapacitance . This hypothesis was also supported by the roughly equivalent size properties of the three comonomers (Table ), as well as the comparable homogeneous cyclic voltammogram responses (Figure a) and calculated diffusion coefficients (Figure b and Table S1) of the resulting copolymers in organic media, all of which imply that the aforementioned dissimilarities in heterogeneous electrochemical behavior between the polymers are not a result of molecular size or electronic properties.…”
Section: Resultssupporting
confidence: 73%
“…The P­(VFc n - co -X 1– n ) ferrocene polymers were prepared through free-radical polymerization of vinylferrocene (VFc), either with or without a comonomer using a previously reported synthesis procedure, developed based on previously reported methods. ,,, The selected comonomer, X, was either styrene (St), methyl methacrylate (MMA), or 2-hydroxyethyl methacrylate (HEMA). Briefly, the polymers were synthesized in anhydrous 1,4-dioxane at 70 °C using 2,2′-azobis­(2-methylpropionitrile) as the radical initiator at ca.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations